Respiratory Management of Newborns - Aly, Hany; Abdel-Hady, Hesham (IntechOpen, 2016)
In this book, you'll learn multiple new aspects of respiratory management of the newborn. For example, ventilator management of infants with unusually severe bronchopulmonary dysplasia and infants with omphalocele is discussed, as well as positioning of endotracheal tube in extremely low birth weight infants, noninvasive respiratory support, utilization of a protocol-driven respiratory management, and more. This book includes a chapter on noninvasive respiratory function monitoring during chest compression, analyzing the efficacy and quality of chest compression and exhaled carbon dioxide. It also provides an overview on new trends in the management of fetal and transitioning lungs in infants delivered prematurely. Lastly, the book includes a chapter on neonatal encephalopathy treated with hypothermia along with mechanical ventilation. The interaction of cooling with respiration and the strategies to optimize oxygenation and ventilation in asphyxiated newborns are discussed.